Critical velocity with and without the application of swimming fins among youth fin competitors - Thanopoulos, V.; Dopsaj, M.; Georgija, R.; Okicic, T. (Facta Universitatis: Series Physical Education and Sport, 2010)
In this study we aimed to define critical velocity among male and female swimmers by means of the application of swimming fins. The sample in this study consisted of 10 Greek freestyle short distance swimmers. The participants swam distances of 25m, 50m, 100m and 200m freestyle with maximum intensity. The start of each test was from the water and always under the same conditions. Critical velocity was calculated according to the performance for each distance (Wakayoshi et al., 1993) and the time needed. For the statistical analysis, the MANOVA analysis was used. The results of this study showed that critical velocity calculation if significantly affected by the type of technical swimming, with a greater critical velocity in the case of swimming with fins between the genders. The type of technical swimming should be taken into consideration in the planning process of fin swim training especially in the case of pre-pubescent children. In addition, male swimmers were shown to have a higher cV when swimming with fins at a swimming distance ranging from 50 to 200 meters (Wilks' Lambda 0.0289, p = 0.015). This may indicate that young males use the fins in a more effective way than the female ones between the ages of 10 and 12.